A Reclamação como via de acesso de submissão das decisões dos juizados especiais cíveis ao crivo do Superior Tribunal de Justiça - Martins, Renata Cristina Lopes Pinto (2019)
The thesis presented consists of the proposal to admit the use of the Institute of the Complaint as a means to submit the decisions rendered by the Special Civil Courts to the control of the Superior Court of Justice when they violate its jurisprudence already signed. In order to support it, the work seeks to analyze certain institutes that are correlated with it: the procedure adopted by the Special Civil Courts, the use of precedents in the Brazilian civil proceeding and the institute of the complaint itself. In this way, it begins analyzing the rite of the Special Courts, in its conceptual and procedural plans, highlighting its recursal system. Afterwards, we will investigate the lack of special appeal in the scope of the Special Civil Courts, as well as its limited appeal system. Finally, we will deal with the institute of the complaint and the possibility of its use as a form of control of the decisions rendered by the Special Civil Courts by the Superior Court of Justice